2007
DOI: 10.1002/jemt.20512
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes of NADPH‐diaphorase‐positive neurons in the rat inferior colliculus and auditory cortex

Abstract: Nitric oxide (NO) has been implied in age-related changes of the central nervous system (CNS) and the central auditory pathway. The present study was conducted to investigate whether the number of NO-producing cells and their morphometric characteristics in the inferior colliculus (IC) and the auditory cortex (AC) are changed with the increasing age of the subjects. IC and AC sections of adult and senile Wistar rats were studied using the histochemical detection of NADPH-diaphorase activity (NADPH-d), a marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In previous studies, a significant increase in NADPH-d-positive neurons was reported in the superior olivary nucleus in aged hamsters [37] and rats [40]. Sánchez-Zuriaga et al showed evidence of a decreased area of NADPH-d-positive neurons in the dorsal cortex (DC) of the IC and an age-related loss of NADPH-d-positive neurons in the IC and primary cortical auditory area (Te1) in rats [41]. These changes were related to hearing impairments associated with increasing age.…”
Section: Regional Changes In Nadph-d In the Aging Brainmentioning
confidence: 99%
“…In previous studies, a significant increase in NADPH-d-positive neurons was reported in the superior olivary nucleus in aged hamsters [37] and rats [40]. Sánchez-Zuriaga et al showed evidence of a decreased area of NADPH-d-positive neurons in the dorsal cortex (DC) of the IC and an age-related loss of NADPH-d-positive neurons in the IC and primary cortical auditory area (Te1) in rats [41]. These changes were related to hearing impairments associated with increasing age.…”
Section: Regional Changes In Nadph-d In the Aging Brainmentioning
confidence: 99%
“…For example, the efficacy of GABAergic and glycinergic inhibitory mechanisms declines with age throughout the central auditory system (Caspary et al, , , , , ), and physiological studies in aged animals reveal varying degrees of degradation in the sound‐processing abilities of aged neurons (Mendelson and Rickets, ; Palombi et al, ; Lee et al, ). Interestingly, the expression of calcium‐binding proteins and nitric oxide synthases has also repeatedly been shown to change within the aging auditory system (O'Neill et al, ; Zettel et al, ; Ouda et al, , ; Sanchez‐Zuriaga et al, ; Huh et al, ). The vast majority of this work has been done in nonprimate models; however, physiological studies in primate auditory cortex suggest an analogous age‐related release from inhibition and a broadening in the spatial tuning of neurons (Juarez‐Salinas et al, ; Engle and Recanzone, ).…”
mentioning
confidence: 99%
“…NO also provides regulatory feedback to the NMDA receptor, along with its numerous signaling and modulatory actions (Hopper et al, ). Regardless of the exact purpose of NO in the auditory system, its relative expression consistently changes with age in rodents (Reuss et al, ; Ouda et al, ; Sanchez‐Zuriaga et al, ; Huh et al, ), and, as with PV, primate studies exploring these changes are sparse (Udell et al, ).…”
mentioning
confidence: 99%
“…The parcelation of auditory structures based upon similar organizational characteristics was recently described in rodents and carnivores with cytochrome oxidase and NADPHd (Loftus et al, 2008). In these parallel pathways, the relative density of neurons that express either PV and/or NADPHd have been shown to change with age in rodents and non-human primates (Zettel et al, 1997; Reuss et al, 2000; Ouda et al, 2003, 2008; Sanchez-Zuriaga et al, 2007; Huh et al, 2008; Gray et al, 2013, 2014a,b), and are thought to play a compensatory role in response to decreased output from the cochlea and/or to changes in neuronal excitability (Gray et al, 2014b). …”
Section: Introductionmentioning
confidence: 99%
“…NADPHd has also been shown to co-localize with distinct calcium binding proteins (Yan et al, 1996), and shows age-related changes throughout the auditory system. Age-related changes in the number of the NADPHd positive cells have been found in the cochlear nucleus of macaques (Gray et al, 2014b), the superior olivary complex of macaques (Gray et al, 2013) and chinchillas (Reuss et al, 2000), as well as the inferior colliculus and auditory cortex of rats (Ouda et al, 2003; Sanchez-Zuriaga et al, 2007; Huh et al, 2008). …”
Section: Introductionmentioning
confidence: 99%